Warmblood fragile foal syndrome type 1 mutation (PLOD1 c.2032G>A) is not associated with catastrophic breakdown and has a low allele frequency in the Thoroughbred breed. (4th October 2019) - Bellone, R. R.; Ocampo, N. R.; Hughes, S. S.; Le, V.; Arthur, R.; Finno, C. J.; Penedo, M. C. T.
Summary: Background: Catastrophic fractures are among the most common cause of fatalities in racehorses. Several factors, including genetics, likely contribute to increased risk for fatal injuries. A variant in the procollagen‐lysine, 2‐oxoglutarate 5‐dioxygenase1 gene (PLOD1 c.2032G>A) was shown to cause Warmblood fragile foal syndrome type 1 (WFFS), a fatal recessive defect of the connective tissue. Screening of multiple horse breeds identified the presence of the WFFS allele in the Thoroughbred. PLOD1 is involved in cross‐linking of collagen fibrils and thus could potentially increase the risk of catastrophic breakdown. Objectives: Estimate the frequency of the WFFS allele ( PLOD1 c.2032G>A) and determine if it is a risk factor for catastrophic breakdown in the Thoroughbred. Study design: Case–control genetic study. Methods: Genomic DNA from hair and/or tissue samples was genotyped for the WFFS allele. Fisher's Exact tests were performed to compare allele and carrier frequencies between the case cohort (catastrophic breakdown, n = 22) and several cohorts with no record of injury (n = 138 raced/trained at same track and season and n = 185 older than 7 years and raced during same season), nonracers (n = 92), and a random sample without consideration for racing history (n = 279). Results: The frequency of the PLOD1 c.2032G>A variant in the Thoroughbred breed is low (1.2%). Seventeen of 716 Thoroughbreds tested were carriers (2.4%) and no WFFS homozygotes were detected. Only one catastrophic breakdown case carried the WFFS allele. No statistically significant difference in allele or carrier frequency was identified between case and control cohorts (P>0.05 in all comparisons performed). Main limitations: This study evaluated cases from one single track. Conclusions: This study demonstrated that the PLOD1 c.2032G>A associated with WFFS is present at very low frequency in Thoroughbreds and is not a genetic risk factor for catastrophic breakdown.